COVID-19: The World Community Expects the World Health Organization to Play a Stronger Leadership and Coordination Role in Pandemics Control - Kuznetsova, Lidia (Frontiers in Public Health, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has been accompanied by the return of the concept of national state and exhibited signs of crisis of globalism and liberalism. The pandemic affected most aspects of society and human activity, including socioeconomic impact. Economic problems, shortages of medical supplies and personnel, xenophobic sentiments, and misinformation led to the use of unethical practices and human rights violations. To navigate through this crisis, many countries resorted to traditional diplomacy in the absence of effective international instruments. Thus, the world faced the urgent need in functioning global governance. The pandemic also manifested the increasing importance of international organizations as sources of technical expertise, providing scientific basis for politicians to legitimize their decisions and actions. The article addresses the topic of implications of the pandemic for governance and forecasting a post-pandemic future. The research focus of this paper, therefore, is the assessment of the role of the World Health Organization (WHO) in prevention and response to pandemics. The work is aimed at identifying the functions of the WHO and assessing its activities in prevention and control of pandemics and response to the COVID-19 pandemic in particular. Furthermore, the objective of this article is to identify gaps in the WHO pandemic control efforts and formulate recommendations on addressing them.